Grandparent-Headed Families in University-Assisted Community Schools: Application of Social Capital Theory. Issue 2 (20th February 2023) - Lee, Youjung; Young, Sarah R
Abstract: University-assisted community schools (UACS), which work as partnerships between schools and universities that assist the mobilization of coordinated services to children, families, and communities, can build capacity for schools and neighborhoods to better serve the needs of marginalized families, such as grandparent-headed households. Despite the increase of grandparents raising grandchildren, school staff are often ill equipped with the necessary skills and resources to support these children and their caretakers, who have multifaceted needs and complicated family contexts. In this conceptual article, the authors utilize social capital theory to propose social work practice implications for implementing UACS to support grandparent-headed families, focusing on three target areas: (1) social obligation and social trust, (2) network and information flow, and (3) norms and effective sanctions. The UACS model can be a vehicle for building social trust among grandparent-headed families, schools, and local communities that can lead to a shared model for grandchildren's academic success. Strengthened networks and information flows are necessary to enhance engagement with these marginalized caregivers. Last, details of how to create norms of cooperation that utilize grandparent-headed families as partners and experts are suggested for effective implementation of the UACS model that engages grandparent-headed families.